2020
DOI: 10.1136/bmjopen-2020-040448
|View full text |Cite
|
Sign up to set email alerts
|

‘Immunity Passports’ for SARS-CoV-2: an online experimental study of the impact of antibody test terminology on perceived risk and behaviour

Abstract: ObjectiveTo assess the impact of describing an antibody-positive test result using the terms Immunity and Passport or Certificate, alone or in combination, on perceived risk of becoming infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and protective behaviours.Design2×3 experimental design.SettingOnline.Participants1204 adults from a UK research panel.InterventionParticipants were randomised to receive one of six descriptions of an antibody test and results showing SARS-CoV-2 antibodi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 14 publications
(11 reference statements)
2
24
0
Order By: Relevance
“…Immunity Certi cation: from antibody testing An online experiment carried out in the UK in April 2020 (n=1204) found that 85% would de nitely (56%) or probably (29%) have an antibody test if offered [47].…”
Section: Uptake Of Tests and Vaccinationmentioning
confidence: 99%
“…Immunity Certi cation: from antibody testing An online experiment carried out in the UK in April 2020 (n=1204) found that 85% would de nitely (56%) or probably (29%) have an antibody test if offered [47].…”
Section: Uptake Of Tests and Vaccinationmentioning
confidence: 99%
“…As more tests move towards FDA approval of home use, clear scienti c communication about the result interpretation becomes more crucial (23,39). A positive serological result does not necessarily mean active infection (23,31,49). Although combined use of molecular and seroconversion results can be used to con rm the diagnosis of symptomatic and hospitalized individuals (35), a positive serological test in the absence of symptoms dissociates the presence of the antibodies from the time of infection (44).…”
Section: Discussionmentioning
confidence: 99%
“…A false positive serological test result may prematurely instill con dence that one has immunity against SARS-CoV-2 infection, thus resulting in behavioral changes that increase risk of transmission (50). Hence, the probability that a person without antibodies will test negative on a serological test is more important than test sensitivity (48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…As more tests move towards FDA clearance for home use, clear scientific communication about the result interpretation becomes more crucial 31, 49. A positive serological result does not necessarily mean active infection 31, 41, 60 . Although combined use of molecular and seroconversion results can be used to confirm the diagnosis of symptomatic and hospitalized individuals 45 , a positive serological test in the absence of symptoms dissociates the presence of the antibodies from the time of infection 54 .…”
Section: Discussionmentioning
confidence: 99%
“…A false positive serological test result may prematurely instill confidence that one has immunity against SARS-CoV-2 infection, thus resulting in behavioral changes that increase risk of transmission 61 . Hence, the probability that a person without antibodies will test negative on a serological test is more important than test sensitivity 59, 60, 61 .…”
Section: Discussionmentioning
confidence: 99%